Characterizing the Mechanical Performance of a Bare-Metal Stent with an Auxetic Cell Geometry - Sukhwinder K. Bhullar; Huseyin Lekesiz; Ahmet Abdullah Karaca; Yonghyun Cho; Stephanie Michelle Willerth; Martin B. G. Jun (Applied Sciences, 2022)
This study develops and characterizes the distinctive mechanical features of a stainless-steel metal stent with a tailored structure. A high-precision femtosecond laser was used to micromachine a stent with re-entrant hexagonal (auxetic) cell geometry. We then characterized its mechanical behavior under various mechanical loadings using in vitro experiments and through finite element analysis. The stent properties, such as the higher capability of the stent to bear upon bending, exceptional advantage at elevated levels of twisting angles, and proper buckling, all ensured a preserved opening to maintain the blood flow. The outcomes of this preliminary study present a potential design for a stent with improved physiologically relevant mechanical conditions such as longitudinal contraction, radial strength, and migration of the stent.